(untitled) (Research, Society and Development, 2022)
The main objective of this research is to investigate the conception of mathematics teachers about the Teaching of Geometry and their experience with the Gestalt Theory in initial and continuing education. As a methodological instrument, we used a questionnaire that was prepared in Google Forms with ten (10) questions, nine (08) being objective and two (02) dissertations on the Teaching of Geometry and Gestalt Theory. Twenty-one mathematics teachers who teach in public and private schools in the state of Paraíba participated. We performed a descriptive analysis of the collected data. The results indicated that the teachers interviewed perceive the importance of Teaching Geometry and recognize the difficulties of teaching this area in the field of mathematics. The interviewees also emphasize that the Gestalt Theory is an alternative to mediate the Teaching of Geometry, but reported that most mathematics teachers do not have knowledge about this theory, during initial and continuing education. We conclude that the Gestalt theory has elements that can enhance the teaching-learning process of geometry, in addition to bringing the student closer to their reality.